Globalization and social protests: where and how? The case of Canada and France - Dufour, Pascale (Revue Gouvernance / Governance Review, 2005)
Although, in these times it could be considered a good “marketing” strategy to discuss globalization, it is increasingly difficult to choose how to address it, given the abundance of literature that has been produced concerning this subject. In this paper, we do not seek to address economic globalization or the objective trends of globalization that occur in the economic sphere. Moreover, we do not analyze globalization as an external factor that can contribute to national economic development, nor as a hegemonic economic force preventing societal development. In other words, the term globalization, as used, is not a causal factor. Instead, this paper attempts to apprehend the relationship between globalization as a new space of social protest (a space of action, as well as an issue of discourses) in two countries : Canada and France. We observe that the fight for global justice is embedded in national contexts, each of which uniquely translates the global problematic. The role of the state is particularly central to an understanding of this variation. In the same way, globalization, as a space of debates and conflicts, affects the form of national social protest, modifying both its frame and scale.